Response Prediction to Methylphenidate in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The pattern of individual responses to methylphenidate (10 mg) and factors that predict drug response in 46 children, 6-13 years old, with attention-deficit hyperactivity disorder (ADHD) were examined at the Department of Child and Adolescent Psychiatry, and the Rudolf Magnus Institute for Neurosciences, University of Utrecht, The Netherlands.